Feeling less alone online: patients' ambivalent engagements with digital media. Issue 6 (11th June 2020) - Petersen, Alan; Schermuly, Allegra; Anderson, Alison
Abstract: Digital media offer the chronically ill, especially those who experience related isolation, unparalleled opportunities to connect with others. This article asks, how do these individuals ascribe meaning to and use these media to manage their condition and related isolation? Using the concepts of affordance and emotional community, and drawing on the findings from an Australian study on patients' use of digital media, we examine individuals' ambivalent ascriptions of media, which are both feared and distrusted for the risks they present and embraced as invaluable tools of social connection. We argue that this ambivalence is explicable in terms of the communities to which the chronically ill belong which are founded on strong emotional bonds. In a context in which individuals tend to feel isolated through pain and/or stigmatisation, digital media may offer powerful means for sharing and affirming their experiences, the subjective benefits of which may outweigh the perceived risks. The article discusses the functions and features of digital media that the chronically ill value and distrust and concludes by considering the implications of our analysis for strategies to address the needs of people who feel isolated as a consequence of their condition.